Co/Zn bimetallic organic framework nanoparticles on carbon fibers as cathode for a high-performance rechargeable aqueous Zn-ion hybrid supercapacitor. (1st March 2023) - Chen, Xiaoyu; Li, Yifeng; Li, Ling; Zhu, Qiancheng; Liang, Baolai; Zhao, Jie; Zhang, Wenming
Abstract: Zinc-ion hybrid supercapacitors (ZHCs) are attracting more attentions due to their high energy/power densities and safety. Pseudocapacitive materials can provide larger capacitances than carbon materials due to their specific faradaic processes. Metal-organic frameworks with good electronic conductivity and abundant redox functional groups are ideal cathodic materials. Herein, a bimetallic organic framework cathode (Co/Zn-ZIF(M24)@CC) is proposed as a high-performance cathode in Zn-ion hybrid supercapacitor. The Co/Zn-ZIF(M24)@CC cathode benefits from a dual-ion storage mechanism of the pseudocapacitive behavior of H + and the electrical double-layer capacitance behavior of Zn 2+, which is methodically explored by ex situ electroanalytic characterizations. The as-prepared Co/Zn-ZIF (M24)@CC electrode achieved the highest energy density of 124.6 Wh kg −1 at 49.2 W kg −1 . This study lays the foundation for the rational design of metal-organic cathodes in ZHCs. Graphical abstract: Image, graphical abstract